Adjunctive buccal and palatal corticotomy for maxillary expansion in a sheep model / Le Huy Thuc My - Le Huy , Thuc My (2019)
The prevalence of transverse maxillary deficiency is high and the number of adults seeking treatment is increasing in the recent years. Untreated patients suffer from psychological and functional problems which resulted in them experiencing inferior quality of lives. Currently, both conventional maxillary expansion and surgically assisted maxillary expansion could not fulfill the needs of the patients as well as the outcomes expected by the clinicians. The purpose of this project is to explore the potential of adjunctive buccal and palatal corticotomy (ABPC) as an alternative intervention for adult maxillary expansion by using a sheep model. Cone beam computed tomography (CBCT) scan has been shown to produce accurate images and 3D volume rendering, thus this study utilised CBCT images to evaluate the dental and skeletal changes before and after intervention and compared the differences of the intervention effects between ABPC assisted rapid maxillary expansion (ABPC + RME group or Group 1), conventional rapid maxillary expansion (conventional RME group or Group 2) and those receiving no intervention (control group or Group 3). Our findings suggested that ABPC + RME allows for both skeletal and dental expansion, with the amount of dental expansion exceeding that of skeletal expansion at the alveolar crest and hard palate levels by two and three folds, respectively. Moreover, skeletal and dental expansion in the ABPC + RME group were approximately three times greater than that of the conventional RME group. As the quality of bone might affect the stability of teeth in their new positions, this study employed micro-computed tomography to assess the bone microstructure recovery at 4- and 12-week retention. After 4 weeks retention, bone volume fraction at the third premolar area were at the lowest value (54.4%-60.39% of the control value) and highest at the first premolar of ABPC + RME group (80.44% of the control value). iv After 12 weeks post-retention, the bone volume fraction value increased up to around 80% of control value. Furthermore, pooled bone volume fraction of the banded teeth in Group 1 was significantly higher than that of Group 2. Therefore, ABPC assisted expansion is less detrimental to the supporting bone of the banded teeth while conventional RME seemed to be harmful to this bone. Histomorphological analysis showed that new bone formation area in Group 1 is around two to three times that of Group 2 and control group. Microvascularisation in the furcation of premolars in Group 1 was significantly higher than that of Group 2 at 4-week. At 12-week retention, this value in Group 1 was still slightly higher than that of Group 2. In conclusion, ABPC + RME allows for both skeletal and dental expansion. Moreover, it also promoted bone remodelling after the intervention. Therefore, ABPC could be a potentially good alternative to the currently available interventions in enhancing the outcomes of maxillary expansion in non-growing subjects.